Experimental hybridization and reproductive isolation between two sympatric species of tephritid fruit flies in the Anastrepha fraterculus species group. (8th August 2017) - Rull, Juan; Tadeo, Eduardo; Lasa, Rodrigo; Rodríguez, Christian L.; Altuzar‐Molina, Alma; Aluja, Martín
Abstract: Among tephritid fruit flies, hybridization has been found to produce local adaptation and speciation, and in the case of pest species, induce behavioral and ecological alterations that can adversely impact efficient pest management. The fraterculus species group within Anastrepha (Diptera: Tephritidae), is a rapidly radiating aggregate, which includes cryptic species complexes, numerous sister species, and several pest species. Molecular studies have highlighted the possibility of introgression between A . fraterculus and A. obliqua . Reproductive isolation has been studied among morphotypes of the A. fraterculus species complex as a tool for species delimitation. Here we examined the existence and strength of prezygotic and postzygotic isolation between sympatric populations of two closely related species within the highly derived fraterculus group ( A. fraterculus and A. obliqua ), coexisting in nature. Although adults of both species showed a strong tendency for assortative mating, a small proportion of hybrid pairings in both directions were observed. We also observed asymmetric postzygotic isolation, with one hybrid cross displaying a strong reduction in fecundity and F1 egg fertility. Survival was greater for the progeny of homotypic and hybrid crosses in the maternal host. There was a marked female biased sex ratio distortion for both F1 hybrid adults. Hybridization between A. fraterculus and A. obliqua in nature may be difficult but possible; these two species display stronger reproductive isolation than all pairs of species previously examined in the A. fraterculus species complex. Asymmetric postzygotic isolation is suggestive of Wolbachia mediated cytoplasmic incompatibilities that may be exploited in area‐wide pest management.